2014
DOI: 10.18011/bioeng2014v8n2p166-172
|View full text |Cite
|
Sign up to set email alerts
|

PODER CALORÍFICO DA MADEIRA DE Eucalyptus grandis E DA Hevea brasiliensis

Abstract: RESUMOA biomassa é todo o material orgânico que, quando queimado, libera alguma forma de energia. Para utilização da biomassa é necessário conhecer o seu poder calorífico que está diretamente relacionada com o teor de umidade no combustível. O objetivo deste estudo é determinar o poder calorifico superior das espécies de Eucalyptus grandis e Hevea brasiliensis, visando conhecer seu potencial energético. Foi determinado o teor de umidade pelo método gravimétrico e poder calorifico superior através de uma bomba … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
1
1
Order By: Relevance
“…The biochar of the pequi sample did not show satisfactory values of surface area (BET and Langmuir) and micropore size (Table 3) when compared with activated carbon from other biomasses. According to the guidelines for the certification of the biochar (European Biochar Certificate version 4.8), the minimum specific surface area required is >150 m 2 /g [39]. In the present study, the minimum value required by the standard was not reached.…”
Section: Biocharcontrasting
confidence: 57%
“…The biochar of the pequi sample did not show satisfactory values of surface area (BET and Langmuir) and micropore size (Table 3) when compared with activated carbon from other biomasses. According to the guidelines for the certification of the biochar (European Biochar Certificate version 4.8), the minimum specific surface area required is >150 m 2 /g [39]. In the present study, the minimum value required by the standard was not reached.…”
Section: Biocharcontrasting
confidence: 57%
“…However, Muzel et al (2014) reported Brazilian forest species that presented higher HHV and were, therefore, widely used for energy generation, as noted by the author above. Studying the wood of clones of Eucalyptus grandis and H. brasiliensis, Telmo and Lousada (2011) reported HHV of 17895 kJ•kg -1 and 17897 kJ•kg -1 .…”
Section: Chemical and Energetic Properties Basic Density And Fiber An...mentioning
confidence: 82%